Shale Gas Revolution: An Opportunity for the Production of Biobased Chemicals? - Bruijnincx, Pieter C. A.; Weckhuysen, Bert M. (Angewandte Chemie International Edition, 2013)
Saying a (bio)mass for the future: The shale gas revolution will strongly impact the availability of a number of key building blocks of the chemical industry, in particular butadiene and aromatics. These developments provide an opportunity for the on‐purpose production of these bulk chemicals from renewable resources, such as biomass. Current efforts and developments from industry and academia in this direction are highlighted.